Integrated use of herbicide and crop mulch in suppressing weed growth in a dry-seeded rice system - Chauhan, Bhagirath Singh; Abugho, Seth Bernard (Scientific Research Publishing, Inc., 2013)
Dry-seeded rice production systems are increasing in many Asian countries because of labor and water scarcities. However, weeds are the main biological constraints in these systems. Herbicides are widely used to manage weeds but they do not provide effective weed control. The use of crop residue as mulch can suppress weed emergence and weed biomass but mulch alone does not provide effective weed control. The integrated use of herbicide and mulch, however, could provide more effective and sustainable weed control in dry-seeded rice systems. A study was conducted in two consecutive rice growing seasons to evaluate the combined effect of herbicide (treated and nontreated) and rice straw mulch (0, 2, and 4 t.ha-1) on weed growth and rice yield in a dry-seeded rice system. In the nontreated plots, weed biomass decreased with increases in mulch amounts, whereas weed biomass in the herbicide-treated plots was similar at different mulch amounts. Overall, herbicide treatments provided better weed control than the mulch treatments. In the nontreated plots, grain yield was similar at different mulch amounts, whereas grain yield in the herbicide-treated plots was greater when the field was mulched with 4 t.ha-1 of rice straw than with no mulch or mulched with only 2 t.ha-1 of rice straw. The results suggest that integrated use of mulch and herbicides can help weed control and increase crop yield in dry-seeded rice.